All Days 2012
DOI: 10.2118/151235-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dynamic Behavior of Bottom Hole Assemblies Containing an Underreamer

Abstract: Reaming while drilling can be a more economical drilling technique than conventional drilling. Downhole failures can occur for a variety of reasons, and failure as a result of excess dynamic loading on the bottom hole assembly (BHA) components may be the most mysterious. One of those mysteries is the static and dynamic distribution of axial load between the bit and the reamer. This paper presents an approach using the explicit finite element method to model the static and dynamic interactions between the bit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…From the base case analysis, it was found that the downhole RPM fluctuation increases for RWD when the bit and reamer experience the same load (Figure 3). This behavior agrees with the finding in Ishak et al 24 Further analysis showed an increase in stick-slip severity for reaming only, i.e. hole opening scenario when applying the same axial load as drilling.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From the base case analysis, it was found that the downhole RPM fluctuation increases for RWD when the bit and reamer experience the same load (Figure 3). This behavior agrees with the finding in Ishak et al 24 Further analysis showed an increase in stick-slip severity for reaming only, i.e. hole opening scenario when applying the same axial load as drilling.…”
Section: Discussionsupporting
confidence: 91%
“…Figures 3 and 4 show the simulated angular velocities and resultant downhole torques for the three cases. It can be seen that the downhole RPM fluctuation increases for Case 1-RWD compared to conventional drilling (Case 2); this behavior agrees with the simulation's behavior seen in Ishak et al 24 Case 3-Reaming without drilling shows the highest downhole RPM fluctuations and indicates stick-slip behavior as seen in the rotational speed behavior (Figure 3) and the resultant torque behavior (Figure 4). As the reamer comes to a complete sticking phase, the reamer's torque spikes up to the maximum available torque and drops to zero during the slip phase.…”
Section: Base Casesupporting
confidence: 85%
See 1 more Smart Citation
“…It can guide the operator to choose the suitable drilling tools and operation parameters. [19][20][21][22] This method is also very useful for a horizontal run or directional run. [23][24][25][26] All works mentioned earlier made great contributions to the application of hole-enlargement technology.…”
Section: Introductionmentioning
confidence: 99%